Dampak Keterlibatan dan Monitoring Terhadap Kecenderungan untuk Melakukan Eskalasi Komitmen - Hariman Bone (Department of Accounting-Faculty of Economic and Business (FEB), 2020)
Balance scorecard (BSC) provides objective, measures, targets and initiatives within each perspective to support the achievement of the company’s vision and strategy. Management involvement in strategic initiatives setting in each perspective allows management to keep running the initiative even though the initiative hinders the achievement of goals. This study examined experimentally the effect of management involvement in strategic initiative setting and monitoring on escalation of commitment. We used 2 X 2 between subjects. The Anova result showed that management involvement could encourage participant in escalation of commitment for failed initiatives